Dynamic approach for spectrum sharing in cognitive radio - Shakor Mahmood, Zuhair; Najdet Nasret Coran, Ali; Esam Kamal, Ayoub (International Journal of Engineering and Technology, 2019)
Due to fixed spectrum allocation phenomenon (FSA), spectrum agreement failed to satisfy the demanded of the evolving technolo-gies. However, cognitive radio has approached for utilizing the spectrum and substituting resources deficiency. The number of radio users is tragically increasing since human turns technologies in all sectors; even those users of licensed band are demanding larger radio spectrum. Users may get assigned into other bands to balance the radio spectrum congestion. In this paper, we proposed model to overcome radio deficiency. This paper is highlighting the spectrum sharing performance constrains. Time delay and throughput are studied under different spectrum sharing techniques.Â Â Â